Lighting loads susceptibility to voltage sag - Ezly Azril Khalid (Universiti Malaysia Perlis, 2009)
One of the common power qualities problems that are major concern in this study is called voltage sag. Voltage sag disturbances, or momentary decreases in voltage, are considered to be the most prominent power quality problem. Voltage sag is a short-term decrease in voltage lasting anywhere from milliseconds up to a few seconds. It can cause malfunction, miss operation and less reliability of the equipment. There are many types of lighting loads that are being used nowadays in industrial and in residential such as fluorescent lamp, high intensity discharge such as metal halide and mercury vapor lamp and incandescent lamp. When voltage sag occurs, it can reduce the performance of those lamps such as the lamps needs time to stabilize for several minutes or the lamp fail to reignite after supply recovery thus it will effect on the economy progress where it make unattractive infrastructure for the investors. In this research, Schaffner Profline 2100 was used to generate voltage sag to the equipment under test (EUT) which is a lighting load. This report will describe about voltage sags and the effects of voltage sag on different type of lighting load and also mitigation method to overcome voltage sags thus protect utility and end user equipment from failing or miss-operating. From the experiment, there are four conclusion that been made based on the observation on the effect on the lamp, the relationship between the duration and the depth of sag, the sensitivity of equipment for voltage sag from the standard (IEC 61000-4-11/IEC 61000-4-34, SEMI F47 and CBEMA (ITI) Curve) and the current spike that occurs. Eventually, when voltage sag happened, a current spike occurs and the current are exceeding the rated current thus can damaging the equipment.